Spontaneous and Induced Lipid Peroxidation in the Yellow Mealworm Tenebrio molitor after Cold Acclimation - Gulevsky, A. K.; Ryazantsev, V. V.; Grischenkova, E. A.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2002)
The content of lipid peroxidation (LPO) intermediates: conjugated dienes and ketodienes, at cold-sensitive and cold-tolerant developmental stages in the yellow mealworm T. molitor was investigated. Intensity of spontaneous and cumil peroxide-induced LPO was estimated. It has been shown that cold-tolerant 8-10 instar larvae are characterised by the reduced LPO product level as a result of cold acclimation. Cold-tolerant larvae are able to â€œhinderâ€ LPO processes preventing accumulation of ketone products.